Construction of Hierarchically Porous Nanoparticles@Metal–Organic Frameworks Composites by Inherent Defects for the Enhancement of Catalytic Efficiency. Issue 49 (10th October 2018) - Meng, Fanchen; Zhang, Suoying; Ma, Lu; Zhang, Weina; Li, Matthew; Wu, Tianpin; Li, Hang; Zhang, Tao; Lu, Xiaohua; Huo, Fengwei; Lu, Jun
Abstract: Nanoparticles@metal–organic frameworks (MOFs) composites have attracted considerable attention in recent years due to the prominent selective catalytic activity. However, it is highly desirable to develop a simple and universal way to settle the trade‐off between the catalytic efficiency and selectivity. Herein, by employing the thermal instability of inherent defects, hierarchically porous Pt@UiO‐66‐NH2, Pt@UiO‐66, Pt@ZIF‐8, and Au@ZIF‐8 are successfully constructed after annealing at an appropriate temperature, respectively. The generated mesopores in the MOFs can be located around the external nanoparticle to retain the MOF shell for catalytic selectivity. Finally, when tested in olefin hydrogenation, Pt@UiO‐66‐NH2 shows significantly improved catalytic rate and enhanced dynamic selectivity. Abstract : A series of nanoparticles@metal–organic frameworks (MOFs) composites with hierarchical porosity is achieved by employing the thermal instability of inherent defects of the nanoparticles@MOFs. The generated mesopores can be located around the external nanoparticles to retain the MOF shell for catalytic selectivity. When tested in olefin hydrogenation, the resulting nanoparticles@MOFs composites exhibit improved catalytic rate and enhanced dynamic selectivity.